Broadening horizons: the role of ferroptosis in polycystic ovary syndrome - Wang, Min; Zhang, Bo-Qi; Ma, Shuai; Xu, Ying; Zhao, Dong-Hai; Zhang, Jing-Shun; Li, Chun-Jin; Zhou, Xu; Zheng, Lian-Wen (Frontiers in Endocrinology, 2024)
Polycystic ovarian syndrome (PCOS) is a common heterogeneous reproductive endocrine metabolic disorder in women of reproductive age characterized by clinical and biochemical hyperandrogenaemia, ovulation disorders, and polycystic ovarian morphology. Ferroptosis is a novel type of cell death driven by iron accumulation and lipid peroxidation. Ferroptosis plays a role in maintaining redox balance, iron metabolism, lipid metabolism, amino acid metabolism, mitochondrial activity, and many other signalling pathways linked to diseases. Iron overload is closely related to insulin resistance, decreased glucose tolerance, and the occurrence of diabetes mellitus. There is limited research on the role of ferroptosis in PCOS. Patients with PCOS have elevated levels of ferritin and increased reactive oxygen species in ovarian GCs. Studying ferroptosis in PCOS patients is highly important for achieving personalized treatment. This article reviews the progress of research on ferroptosis in PCOS, introduces the potential connections between iron metabolism abnormalities and oxidative stress-mediated PCOS, and provides a theoretical basis for diagnosing and treating PCOS.